Answer:
Step-by-step explanation:
![\frac{dy}{dx}=x^{2}(y-1)\\\frac{1}{y-1} \text{ } dy=x^{2} \text{ } dx\\\int \frac{1}{y-1} \text{ } dy=\int x^{2} \text{ } dx\\\ln|y-1|=\frac{x^{3}}{3}+C\\](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%3Dx%5E%7B2%7D%28y-1%29%5C%5C%5Cfrac%7B1%7D%7By-1%7D%20%5Ctext%7B%20%7D%20dy%3Dx%5E%7B2%7D%20%5Ctext%7B%20%7D%20dx%5C%5C%5Cint%20%5Cfrac%7B1%7D%7By-1%7D%20%5Ctext%7B%20%7D%20dy%3D%5Cint%20x%5E%7B2%7D%20%5Ctext%7B%20%7D%20dx%5C%5C%5Cln%7Cy-1%7C%3D%5Cfrac%7Bx%5E%7B3%7D%7D%7B3%7D%2BC%5C%5C)
From the initial condition,
![\ln|3-1|=\frac{0^{3}}{3}+C\\\ln 2=C](https://tex.z-dn.net/?f=%5Cln%7C3-1%7C%3D%5Cfrac%7B0%5E%7B3%7D%7D%7B3%7D%2BC%5C%5C%5Cln%202%3DC)
So we have that ![\ln |y-1|=\frac{x^{3}}{3}+\ln 2\\e^{\frac{x^{3}}{3}+\ln 2}=y-1\\2e^{\frac{x^{3}}{3}}=y-1\\y=2e^{\frac{x^{3}}{3}}+1](https://tex.z-dn.net/?f=%5Cln%20%7Cy-1%7C%3D%5Cfrac%7Bx%5E%7B3%7D%7D%7B3%7D%2B%5Cln%202%5C%5Ce%5E%7B%5Cfrac%7Bx%5E%7B3%7D%7D%7B3%7D%2B%5Cln%202%7D%3Dy-1%5C%5C2e%5E%7B%5Cfrac%7Bx%5E%7B3%7D%7D%7B3%7D%7D%3Dy-1%5C%5Cy%3D2e%5E%7B%5Cfrac%7Bx%5E%7B3%7D%7D%7B3%7D%7D%2B1)
First calculate total payments
18×95.25=1,714.5
After that to find the interest you just subtract the amount borrowed from the total payments
Interest=1,714.5−1,450=264.5
Hope it helps!
8s-8 is answer
Just distribute
Point two should be your answer
Y = 3x is the answer
I did the math